2010
DOI: 10.1002/eqe.1065
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐based earthquake engineering assessment of a self‐centering, post‐tensioned concrete bridge system

Abstract: Highway bridges in highly seismic regions can sustain considerable residual displacements in their columns following large earthquakes. These residual displacements are an important measure of post-earthquake functionality, and often determine whether or not a bridge remains usable following an earthquake. In this study, a self-centering system is considered that makes use of unbonded, post-tensioned steel tendons to provide a restoring force to bridge columns to mitigate the problem of residual displacements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…However, increases in preload and damping have important effects in reducing the residual drift and the peak story drift, respectively [23]. The former is of particular interest today and is considered an important performance index [41][42][43]. This section concentrates on an evaluation of the performance of structures with and without fluidic self-centering systems based on the residual drift.…”
Section: Residual Drift Fragility Analysismentioning
confidence: 99%
“…However, increases in preload and damping have important effects in reducing the residual drift and the peak story drift, respectively [23]. The former is of particular interest today and is considered an important performance index [41][42][43]. This section concentrates on an evaluation of the performance of structures with and without fluidic self-centering systems based on the residual drift.…”
Section: Residual Drift Fragility Analysismentioning
confidence: 99%
“…This analysis mainly discusses the meaningful value for an owner or decision maker of the structure. This value includes direct pecuniary losses, casualties, and downtime [5]. In the following, a case study is considered to develop fragility curves through the procedure of PEER methodology.…”
Section: -Peer Pbee Analysis Methodologymentioning
confidence: 99%
“…After the pushover analyses, the structural analysis is continued by performing one dynamic analysis. According to previous studies, one of the common dynamic analysis which is well integrated to this frame work, especially when seismic uncertainty is under question, is IDA method [5]. There are two important steps in basis of IDA method.…”
Section: -Structural Analysis and Hazard Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results by Cheng [9] demonstrated that the bridge model could rock up to 5% of the column rotation without damage or residual displacement. In addition, given the increasing interest in self-centering bridge piers, Wacker et al [11] and Lee and Billington [12] also developed design procedures and a seismic assessment method based on the performancebased earthquake engineering framework. Whereas self-centering structures with posttensioned tendons exhibit high performance for eliminating residual displacement, it is also found that this type of structure contains inherent defects of low energy dissipation, which increases the seismic responses of the structures.…”
Section: Introductionmentioning
confidence: 99%